Sharing Data – Not With Us! Distrust as Decisive Obstacle for Public Authorities to Benefit From Sharing Economy - Nienaber, Ann-Marie Ingrid; Woodcock, Andree; Liotopoulos, Fotis K. (Frontiers in Psychology, 2021)
Future mobility planning to cope with ongoing environmental challenges such as air pollution has to be anchored in the work of every public authority worldwide. One recent trend that could support public authorities to meet the European Union’s sustainability targets is the creation and sharing of transport and mobility ‘big’ data between public authorities via tools such as crowdsourcing. While the benefits of the use of big data to increase public authorities’ efficiency and effectivity and their citizen’s lives is well understood, examples from the public sector that highlight public authorities’ engagement in such sharing activities is still missing. To date relevant literature has highlighted issues around the capacity of public authorities that hinder shared activities. In this paper we want to raise distrust as a key reason for lack of engagement. Based on comprehensive data collected over the period of four years via several workshops and semi-structured interviews with seven public authorities in Europe, we are able to demonstrate that a major obstacle for not providing and sharing data via crowdsourcing for mutual benefit lies primarily in the hands of the public authority’s servants of the middle and high-level management. Our results show firstly, that distrust may emerge towards different referents such as the community, particular individuals, or the technology itself and thus, managerial implications have to be very specific to overcome distrust. Secondly, we show how distrust may spread from one referent to another through negative reciprocity and which, if unchecked may lead to an all-encompassing state that affects the whole sharing economy framework and inhibits potential benefits.